ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMP NEGERI 4 TONDANO PADA MATERI BANGUN DATAR PERSEGI DAN PERSEGI PANJANG - Jili Momongan; Anekke Pesik; Derel Filandy Kaunang (Universitas PGRI Sumatera Barat, 2026)
The purpose of this study is to analyze the mathematical conceptual understanding ability of grade VII A students at SMP Negeri 4 Tondano on the topics of squares and rectangles, as well as to identify the influencing factors. This study employs a qualitative descriptive approach with 23 students as research subjects. Data were collected through five essay test items and in-depth interviews. Data analysis followed the Miles and Huberman model through data reduction, data display, and conclusion drawing. Results indicate that students' conceptual understanding is generally in the moderate category. Of 23 students, 5 (21.74%) were categorized as high, 14 (60.87%) as moderate, and 4 (17.39%) as low. Common errors included incorrect use of formulas, computational mistakes, inability to provide examples and non-examples, and difficulty applying concepts to contextual problems. Influencing factors include internal factors (learning motivation, cognitive ability, self-concept) and external factors (teaching strategies, learning environment support, and availability of facilities).